Current Practices and Standards of Cataloging Hebraica in RLIN - Lerner, Heidi (Judaica Librarianship, 1994)
Since 1988, approximately 21 institutions have input Hebraica records into RLIN utilizing its Hebrew script capability. These institutions have varying standards for the amount of Hebrew script and Romanization that they provide. Some institutions provide vernacular access only for the core fields that have been defined by RLIN; others provide vernacular access for main and ad d ed entries, notes, and subject headings as well. Some institutions do not provide Romanization for the statement of responsibility or beyond the title proper. These institutions have varying financial, technical, and policy constraints that have contributed to this diversity of procedures for inputting vernacular records and for vernacular enhancement of already existing copy. In the papers from the AJL 1993 Convention session on "Modification of RLIN Hebraica Records," we share in each other's experiences in creating and modifying RLIN Hebraica script records.